Writing prompt convergence in high-stakes tests: Exploring rhetorical functions and objects of enquiry. (December 2015) - Liu, Fulan; Stapleton, Paul
Highlights: A hundred and twenty writing prompts in three high-stakes tests were examined. We focused on two elements in a prompt: rhetorical function and object of enquiry. Results revealed that both elements converged over narrow ranges. The convergence in writing prompts may cause prescriptive responses from students. We propose that a wider range of writing prompts be included in high-stakes tests. Abstract: The writing prompts in high-stakes tests have become an issue of concern due to their possible effect on test takers' writing performance and potential washback on writing pedagogy. In the present study, the prompts ( n  = 120) from three of these tests, TOEFL, IELTS and TEM4 (a language test in China), were investigated for two elements – their specific rhetorical function and object of enquiry – to examine whether these prompts displayed certain patterns. Results revealed that both of these elements converged around a narrow set of themes and functions. Specifically, a preponderance of prompts required responses that were either evaluative (44%) or hortative (23%) (recommending). As for the objects of enquiry, three sociocultural themes were dominant: education (34%); technology (20%); and current social issues (15%). These findings may indicate that the prompts in high-stakes tests are converging around a restricted set of themes, which may be generating prescriptive responses that fail to appreciate the full range of linguistic and argumentative possibilities normally expected in academic writing. Here, we propose that a wider range of writing prompts with alternative rhetorical functions and objects of enquiry be considered in high-stakes tests in order to facilitate students' writing and thinking development.